Study on the RBE estimation for carbon beam scanning irradiation using a solid‐state microdosimeter. Issue 2 (2nd December 2019) - Han, Soorim; Yoo, Seung Hoon; Shin, Jae Ik; Kim, Eun Ho; Jung, Won‐Gyun; Kim, Kum Bae; Matsumura, Akihiko; Kanai, Tatsuaki; Tran, Linh T.; Chartier, Lachlan; James, Benjamin; Rosenfeld, Anatoly B.
Abstract : Purpose: The purpose of this study was to study the field size effect on the estimated Relative Biological Effectiveness (RBE) for carbon scanning beam irradiation. Methods: A silicon‐on‐insulator (SOI) microdosimeter system developed by the Centre for Medical Radiation Physics, University of Wollongong, Australia, was used for lineal‐energy measurements (microdosimetric quantity). The RBE values were derived based on the modified microdosimetric kinetic model (MKM) at different depths in a water phantom in the scanning carbon beam for various scanned areas. Results: Our study shows that the difference in RBE values derived from the SOI microdosimeter measurements with the MKM model and from the Treatment Planning System (TPS). The difference of the RBE values is within 6.5 % at the peak point of the spread‐out Bragg Peak (SOBP) region. Compared to the spot‐beam, RBE values obtained in the scanned‐beam with a larger scanned area of 1.0 × 1.0 cm 2 have better agreement with which estimated by the TPS. Conclusions: This study shows the possibility of using the SOI microdosimeter system as a quality assurance (QA) tool for RBE evaluation in carbon‐pencil beam scanning radiotherapy.